2022
DOI: 10.3390/nu14204418
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Eating Context on Dietary Choices of College Students: Evidence from the HEALTHY-UNICT Project

Abstract: While personal characteristics have been evaluated as determinants of dietary choices over the years, only recently studies have looked at the impact of eating context. Examining eating context, however, can be challenging. Here, we propose the use of a web-app for the Ecological Momentary Assessment of dietary habits among 138 college students from Catania (Italy) and therefore for examining the impact of eating context on dietary choices. Eating away from home was associated with lower odds of consuming vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Some studies ( 10 , 25 ) report that students who live away from home develop worse habits than those who live at home, associating this with a decrease in the intake of home-cooked meals. In a similar vein, a study showed that eating away from home was associated with a lower trend to consume vegetables, fruits and legumes and a higher predisposition to consume processed meat, salty snacks and carbonated beverages ( 15 ) .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some studies ( 10 , 25 ) report that students who live away from home develop worse habits than those who live at home, associating this with a decrease in the intake of home-cooked meals. In a similar vein, a study showed that eating away from home was associated with a lower trend to consume vegetables, fruits and legumes and a higher predisposition to consume processed meat, salty snacks and carbonated beverages ( 15 ) .…”
Section: Discussionmentioning
confidence: 96%
“…There are multiple factors that affect the quality of diet: demographic characteristics, unhealthy behaviours – such as sedentary lifestyle – and family and social influence ( 14 ) . In fact, a possible association has been established between the social context – eating more frequently outside home and accompanied – and changes in dietary habits ( 15 ) . In addition, alcohol consumption is an important aspect in undergraduate students, a population prone to risky alcohol consumption ( 16 , 17 ) .…”
mentioning
confidence: 99%
“…Furthermore, the food habits measurement was not added based on this telephone survey. However, this study focused on the degree of infuence of food habits by COVID-19; hence, it is necessary to use innovative approaches and tools to assess them in the future [27,28], especially in China with more than one billion Internet users. Based on a large-scale survey administered in Wuhan City, the results provide direct evidence for the efects of the pandemic lockdown on BMI and overweight/obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies evaluated the relationship of single nutrients and foods with pregnancy and neonatal outcomes [23][24][25][26][27][28][29][30][31][32][33][34][35][36], these elements are not consumed alone but in complex dietary patterns. To meet the need of capturing the complex interactions between nutrients, foods and other relevant factors, the research is moving to the development of innovative tools for data collection [37][38][39][40][41][42][43][44][45] and to the analysis of dietary patterns, using both a priori and a posteriori methods [46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%